2024
DOI: 10.1126/scisignal.abl3758
|View full text |Cite
|
Sign up to set email alerts
|

CXCL17 is an allosteric inhibitor of CXCR4 through a mechanism of action involving glycosaminoglycans

Carl W. White,
Simon Platt,
Laura E. Kilpatrick
et al.

Abstract: CXCL17 is a chemokine principally expressed by mucosal tissues, where it facilitates chemotaxis of monocytes, dendritic cells, and macrophages and has antimicrobial properties. CXCL17 is also implicated in the pathology of inflammatory disorders and progression of several cancers, and its expression is increased during viral infections of the lung. However, the exact role of CXCL17 in health and disease requires further investigation, and there is a need for confirmed molecular targets mediating CXCL17 functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 57 publications
0
1
1
Order By: Relevance
“…Our obtained K i values of IT1t and AMD3100 for CXCR4 were approximately 1.5-and 30-fold higher, respectively, than previously observed in a NanoBRET-based CXCR4 binding assay versus CXCL12-AF647 [30]. However, a K i value of 10 nM has also been recently reported for AMD3100 in this NanoBRET-based binding assay using CXCL12-AF647 [31], which is only 3-fold lower than observed for the four AZDyelabeled CXCL12 analogs in this study. For burixafor, an IC 50 value of 10 nM in a CXCL12 competition binding assay on human CXCR4 was obtained [32]; this is likely in the same order range as our observed K i value of 25 nM.…”
Section: Inhibition Of Cxcl12-azdxxx Binding To Nluc-ackr3 or Nluc-cx...contrasting
confidence: 50%
“…Our obtained K i values of IT1t and AMD3100 for CXCR4 were approximately 1.5-and 30-fold higher, respectively, than previously observed in a NanoBRET-based CXCR4 binding assay versus CXCL12-AF647 [30]. However, a K i value of 10 nM has also been recently reported for AMD3100 in this NanoBRET-based binding assay using CXCL12-AF647 [31], which is only 3-fold lower than observed for the four AZDyelabeled CXCL12 analogs in this study. For burixafor, an IC 50 value of 10 nM in a CXCL12 competition binding assay on human CXCR4 was obtained [32]; this is likely in the same order range as our observed K i value of 25 nM.…”
Section: Inhibition Of Cxcl12-azdxxx Binding To Nluc-ackr3 or Nluc-cx...contrasting
confidence: 50%
“…Attempts to identify the receptor for CXCL17 remain so far unsuccessful. Recent reports, however, suggested that CXCL17 is a low-affinity agonist for the Mas-related GPR family member X2 (MRGPRX2), a low-selectivity receptor for peptides, and that it could act as an allosteric inhibitor of CXCR4 9,10 . This study establishes GPR182 as a high-affinity receptor also for two biologically active small non-chemokine proteins, GPR15L and CXCL17.…”
Section: Short Reportmentioning
confidence: 99%